Case Report: The Association of Wilson Disease in a Patient With Ataxia and GLUT-1 Deficiency - Diaz, Jenna; Fonseca, Ashley G.; Arboleda, Richard; Frade, Alejandro; Gennaro, Maria Pilar; Jayakar, Parul; Schleifer, Paula; Hernandez, Erick (Frontiers in Pediatrics, 2021)
Background: Wilson disease (WD) and glucose transporter type 1 (GLUT1) deficiency syndrome are two syndromes with different modes of inheritance but share certain similarities on neurological presentation. To date we have not found previous reports of an association between these two disorders. Case presentation: Here we describe a 9-year-old male with global developmental delay that presented with intermittent and sudden onset weakness that first occurred at age 3. He was diagnosed with a mutation in the SLC2A1 (Solute Carrier Family 2 Member 1) gene, which results in GLUT1 deficiency. A ketogenic diet could not be started because of unexplained elevated liver enzymes. Due to his liver enzymes' persistent elevation, further investigations demonstrated mildly decreased ceruloplasmin levels, high basal 24-hour urinary copper excretion, and an elevated hepatic parenchymal copper concentration on liver biopsy, consistent with WD. Genetic testing revealed two separate mutations in the ATP7B (ATPase Copper Transporting Beta) gene, consistent with WD. The patient was treated with a low copper diet, zinc acetate, and trientine hydrochloride. When liver enzymes normalized, he was subsequently started on a ketogenic diet with improvement in neurological symptoms. His neurological symptoms were most likely secondary to GLUT1 deficiency syndrome, as WD's neurological symptoms are primarily observed in the second decade of life. Conclusion: Recent studies have demonstrated the importance of genetic testing upon unexplained persistent elevation of liver enzymes. This case highlights the importance of carefully evaluating a patient with an unexplained liver disorder, even in the presence of primary neurological disease, as it can have significant therapeutic implications.